Opção mágica: conversão de kardecista à umbanda na cidade de Goiânia - BELMONT, Rafael Neves Flôres (2007)
Umbanda is conceived in the connection between popular cults and Spiritism and Candomble, and it is established in the scope of the big towns. For one side, there is a trying of getting white , or civilizing these services putting them together to the kardecist doctrine. For the other side, this doctrine itself has searched in the African sources ritualistic and of possession roots, in a moment of getting black . In this way, making part of these two movements, it appears Umbanda, which nowadays in Brazil can not be seen as homogeneous, but such as a ritualistic and doctrinaire complex that, despite the differences, has kept in itself a ritual and mediúnica line. In other words, the all deformed that we name Umbanda has established as a way of identity a mediunic continuum. In the extremities of this continuum are, by one side, Candomble, on the other side, Spiritism. In this way, talking about the kardecists converting to Umbanda it is to talk about a location changing in the mediunic continuum. To analyze this conversion requests, although, the understanding of how this changing is established in the practice, what doctrinaire and ritualistic elements influence it and how it is deal. So, it was noticed that the ritual is the top of the non-according between the two religions in the present work, Kardecismo and Umbanda. It is in the difference between these rituals, its doctrinaire code, and, mainly in the way of how people participate, that the conversion will settle and solidify.